2016
DOI: 10.1038/srep37927
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Specific Overexpression of Mitochondrial Omi/HtrA2 Induces Myocardial Apoptosis and Cardiac Dysfunction

Abstract: Myocardial apoptosis is a significant problem underlying ischemic heart disease. We previously reported significantly elevated expression of cytoplasmic Omi/HtrA2, triggers cardiomyocytes apoptosis. However, whether increased Omi/HtrA2 within mitochondria itself influences myocardial survival in vivo is unknown. We aim to observe the effects of mitochondria-specific, not cytoplasmic, Omi/HtrA2 on myocardial apoptosis and cardiac function. Transgenic mice overexpressing cardiac-specific mitochondrial Omi/HtrA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Cardiomyocyte apoptosis plays a significant role in the pathology of cardiac damage in the context of myocardial I/R injury, which results in the loss of cardiomyocyte volume and the subsequent cardiac diastolic/systolic dysfunction [31]. Thus, examining ways to attenuate I/R-induced cardiomyocyte apoptosis is of clinical interest to combat myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocyte apoptosis plays a significant role in the pathology of cardiac damage in the context of myocardial I/R injury, which results in the loss of cardiomyocyte volume and the subsequent cardiac diastolic/systolic dysfunction [31]. Thus, examining ways to attenuate I/R-induced cardiomyocyte apoptosis is of clinical interest to combat myocardial I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…With the loss of oxygen supply, cardiomyocytes apoptosis ensues in the hypoxic area, resulting in the downregulation of cardiac function [21,22]. In order to investigate the apoptotic effects in hypoxia cardiomyocytes induced by CoCl 2 , we detected the expressions of Bcl-2 family members (Bax and Bcl-2) and caspase-3 in H9c2 cells.…”
Section: Cocl 2 Induced Apoptosis In H9c2 Cellsmentioning
confidence: 99%
“…these studies indicated that Omi/HtrA2 leads to caspase activation by some different pathways. A recent study reported in vitro mitochondrial Omi/HtrA2 higher expression level promoted cardiomyocyte apoptosis, not involved its translocation from the mitochondria, which might be depended by the inhibitions of the anti-apoptotic mitochondrial protein HAX-1 (Wang et al, 2016). So, the mechanisms involved in mitochondrial dysfunction induced by Omi/HtrA2 should be investigated further.…”
Section: Discussionmentioning
confidence: 99%